Automatic quality control of flow wheat treatment - Diordiiev, Volodymyr; Діордієв, Володимир Трифонович; Диордиев, Владимир Трифонович; Kashkarov, Anton; Кашкарьов, Антон Олександрович; Кашкарев, Антон Александрович; Novikov, Hennadii (Tavria state agrotechnological university, 2017)
The paper analyses the urgency of presowing wheat grain dressing. Measures for automatic control of the technological process of flow grain treatment according to its digital image are proposed. A laboratory method for assessing the treatment quality with the archiving of visually perceptible samples has been implemented. It is also possible to use a hardware method based on the pulse image acquisition, which reduces the requirements for speed and processing power of the control system, but does not allow an operator to visually assess the quality of treatment. A device for obtaining a digital grain image in a pulse mode is proposed. The design of the device takes into account the technological process features of presowing grain processing. As a sensitive element, it has been proposed to use a CCD matrix protected by quartz glass and illumination with a white LED strip or a cold cathode lamp. The developed methods allow for the first time to introduce an automatic method for controlling the operating modes of seed protectants, both with and without the use of dyes. The methods can be implemented in the laboratory with a selected sample from the grain flow, and directly in the grain flow in the automatic mode without physical sampling. The latter minimizes the contact of the operating personnel with the treated seed material. At this stage of laboratory experiments, we can ascertain the dependence of coordinates of the vertex of the approximant parabola on the marker amount that is on the grain surface, which in the context of treatment indicates the protectant amount. In practice, this technique must be adapted to the colour of the dye. The by-side practical result is the possibility of grain contamination control which may indicate a violation of presowing treatment modes.
Keywords: wheat treatment; automatic control; digital image; quality of treatment